2016
DOI: 10.1016/j.tifs.2015.11.008
|View full text |Cite
|
Sign up to set email alerts
|

In vivo antioxidant activity of phenolic compounds: Facts and gaps

Abstract: Background: Numerous diseases have been related with free radicals overproduction and oxidative stress. Botanical preparations possess a multitude of bioactive properties, including antioxidant potential, which has been mainly related with the presence of phenolic compounds. However, the mechanisms of action of these phytochemicals, in vivo effects, bioavailability and bio-efficacy still need research.Scope and Approach: The present report aims to provide a critical review on the aspects related with the in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
170
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(184 citation statements)
references
References 102 publications
5
170
1
8
Order By: Relevance
“…Apart from energetics, oxidation supports immunological integrity. While the bulk of epidemiological evidence supports the nutritional/health value of fruits and vegetables [4,11,12,19,22,33,39,40,50], the doses of individual components they contain, such as specific antioxidants that may contribute to improved health and reduced risk of certain diseases, remain uncertain.…”
Section: Flavonoids -From Biosynthesis To Human Health 206mentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from energetics, oxidation supports immunological integrity. While the bulk of epidemiological evidence supports the nutritional/health value of fruits and vegetables [4,11,12,19,22,33,39,40,50], the doses of individual components they contain, such as specific antioxidants that may contribute to improved health and reduced risk of certain diseases, remain uncertain.…”
Section: Flavonoids -From Biosynthesis To Human Health 206mentioning
confidence: 99%
“…However, the issue of food antioxidants although important is a controversial topic [11,64,72,[363][364][365]. The plethora of published studies on mechanisms [132] that may mediate therapeutic or chemical chemopreventive effects of dietary constituents contrasts sharply with a scarcity of information on their pharmaceutical and clinical-pharmacological properties.…”
Section: Final Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…C-7), 161.1 (C-5), 156.6 (C-9), 148.1 (C-4'), 147.2 (C-2), 145.5 (C-3'), 136.1 (C-3), 122.4 (C-1'), 120,5 (C-6'), 116.0 (C-5'), 115.4 (C-2'), 103.4 (C-10), 98.6 (C-6), 93.8 (C-8) 1 H NMR and 13 C NMR data agree with the data given in the literature for quercetin [15] (Figure 1). The correlation between phenolic compounds and strong antioxidant activity has been showed with many studies up to date [17]. Also it has been known that isoflavonoids show antioxidant activity and some of the beneficial effects of them are reported to be connected with this activity [18].…”
Section: Present Studymentioning
confidence: 95%
“…The most important feature of these compounds is their antibacterial and antioxidant activity [1][2][3][4][5]. Dietary studies have clearly shown a correlation between the content of phenolic compounds in plant foods and a decrease in the incidence of lifestyle diseases [6,7]. From a wide variety of honeys, consumers frequently choose unifloral honeys because their specific medicinal properties are well defined.…”
Section: Introductionmentioning
confidence: 99%